IGHV3-21 gene expression in patients with b-cell chronic lymphocytic leukemia in Ukraine - Abramenko, I.; Bilous, N.; Kryachok, I.; Filonenko, I.; Pilipenko, G.; Chumak, A.; Bazyka, D.; Bebeshko, V. (Experimental Oncology, 2007)
The aim of the study was to evaluate the frequency of IGHV3-21 gene usage and its clinical significance for patients with B-cell chronic lymphocytic leukemia (CLL) in Ukraine. Patients and Methods: Immunoglobulin variable heavy chain (IGHV) gene repertoire was studied in 189 CLL patients using reverse transcribed polymerase chain reaction and direct sequence of amplified products. Results: IGHV3-21 gene expression was found in 11 cases (5.8%), and its frequency was intermediate between Scandinavian (11.7%) and Mediterranean CLL (2.9%) cohorts. The most of cases (9 of 11) belonged to subset with heterogeneous HCDR3 (heteroHCDR3 subset), and only 2 cases – to subset with classical short ARDANGMDV motif (homHCDR3 subset). Six IGHV3-21 cases were mutated and 5 cases were unmutated. All unmutated cases (all were from heteroHCDR3 subset) had similarity of their HCDR3s with previously published sequences. The differences in overall (OS), progression-free (PFS) and treatment-free survival (TFS) for IGHV3-21 positive patients in comparison with CLL patients expressing the other IGHV genes were statistically insignificant. These survival parameters were comparable also for CLL patients with mutated IGHV3-21 gene usage and expression the others mutated IGHV genes. But remarkable feature of IGHV3-21 expressing patients was high incidence of solid tumors. They have developed in 4 IGHV3-21 positive cases (36.4%) and in 10 cases with expression of the others IGHV genes (5.6%, p = 0.0002). Furthermore, in small group of 6 patients with mutated IGHV3-21 gene expression, 3 patients had solid tumors and one underwent Richter transformation. Unmutated IGHV3-21 gene expressed patients had worse OS and PFS in comparison with CLL patients that expressed the others unmutated IGHV genes. Conclusion: Presented data are in agrement with the opinion about negative prognostic significance of IGHV3-21 gene expression regardless its mutation status. IGHV3-21 expression was associated with development of secondary solid tumors. Revealed high level of homology in heteroHDR3s subset might suggest about possible antigenic influence also, in addition to homHCDR3 subset that was proposed earlier. Цель: оценить частоту использования гена IGHV3-21 и его клиническое значение для больных B-клеточным хроническим
лимфолейкозом (ХЛЛ) в Украине. Больные и методы исследования: репертуар генов вариабельных участков тяжелых цепей
иммуноглобулинов (IGHV) изучали у 189 больных с ХЛЛ с помощью полимеразной цепной реакции на базе обратной транскрипции
и прямого сиквенса амплифицированных продуктов. Результаты: экспрессия гена IGHV3-21 выявлена у 11 пациентов (5,8%),
что занимает промежуточное положение между Скандинавской (11,7%) и Средиземноморской (2,9%) когортами. Большинство
случаев (9 из 11) относились к подгруппе с гетерогенным третьим комплементарнымрегионом (heteroHCDR3 подгуппа) и только
2 случая — к подгруппе с коротким классическим ARDANGMDV мотивом (homHCDR уппа). есть IGHV3-21-позитивных
случаев были мутированными и 5 — немутированными. Все немутированные случаи (все из heteroHCDR уппы)
имели сходство HCDR3 с анее описанными последовательностями. Различия в общей выживаемости (OS), длительности
периода до прогрессии заболевания (PFS) и начала лечения (TFS) для IGHV3-21-позитивных больных были статистически
незначимы по сравнению с пациентами с ХЛЛ с экспрессией других IGHV-генов. Указанные параметры также сравнивали
между больными ХЛЛ с экспрессией мутированных IGHV3-21- и других IGHV-генов. Отличительной чертой пациентов с
экспрессией IGHV3-гена была высокая встречаемость солидных опухолей. Они развились в 4 IGHV3-21-позитивных случаях
(36,4%) и в 10 случаях с экспрессией других IGHV-генов (5,6%, p = 0,0002). Кроме того, в небольшой группе больных (6) с
экспрессией мутированного IGHV3-21-гена у 3 возникли солидные опухоли и 1 пациента — синдром Рихтера. У больных с
экспрессией немутированного IGHV3-21-гена определяли худшие показатели OS и PFS по савнению с пациентами с экспрессией
других немутированных IGHV-генов. Выводы: представленные данные согласуются с мнением о самостоятельном
негативном прогностическом значении для больных с ХЛЛ экспрессии IGHV3-21-гена вне зависимости от его мутационного
статуса. IGHV3-21-экспрессия была ассоциирована с развитием вторичных солидных опухолей. Выявленный высокий уровень
гомологии в heteroHDR3s-подгруппе может свидетельствовать о возможном антигенном влиянии в дополнение к антигенному
влиянию в homHCDR уппе, что было установлено ранее